Hubungan Persepsi Siswa Dan Peran Bimbingan Konseling Dengan Minat Memasuki SMKN 1 Mejayan Tahun Pelajaran 2019/2020 - Murniati , Agustina Eka (Yayasan Darusssalam Bengkulu, 2020)
The purpose of this study is 1. to investigate the relationship between students' perceptions and the role of counseling guidance with interest in entering SMK 1 Mejayan; 2. investigate the relationship of students' perceptions with interest in entering SMK 1 Mejayan; 3. Investigate the relationship between students' perceptions and the role of counseling guidance with interest in entering SMK 1 Mejayan; 4. Investigate the relationship between the role of counseling guidance and interest in entering SMK 1 Mejayan. The research method is a survey and quantitative approach. The subjects of the study were students of class X at SMK 1 Mejayan. The population in this study were all class X all majors for the 2019/2020 school year, totaling 726 students. The instrument used in this study was questionnaire distribution. The questionnaire trial was conducted on 30 respondents from one class namely X IPA C. The validity test used the Pearson product moment formula and the reliability test used the alpha formula. Data analysis techniques using multiple predictor double regression analysis techniques and Pearson product moment correlation techniques. The analysis prerequisite tests included: data normality test, linear test and significance of regression, and independent test. Based on the results of the analysis can be concluded, 1). There is a relationship between students' perceptions and the role of counseling guidance towards the interest in entering SMK 1 Mejayan in learning 2019/2020 lessons. Student perception variable made a relative contribution of 83.8% and an effective contribution of 54.1%. The role of counseling guidance variable gave a relative contribution of 16.2% and an effective contribution of 10.5%. 2). There is a correlation between students' perceptions with interest in entering Mejayan 1ND Vocational School. 3). There is a relationship between the role of counseling guidance and interest in entering Mejayan 1ND Vocational School. 4). Student perception variable has a stronger relationship with interest in entering SMK 1 Mejayan. The recommendations that can be given to SMK 1 Mejayan from the conclusions of this study are the need to improve the school promotion strategy to the community and junior high schools through the counseling guidance section because a good promotion strategy will be able to improve the quality of student resources. The research suggestion is adding other independent variables to find out relationship with interest in entering SMK 1 Mejayan.